Peran Lembaga Bantuan Hukum Kepada Masyarakat Tidak Mampu Di Gorontalo Dalam Perkara Kasus Perdata - Monoarfa, Parasya Aidilla; Wantu, Fence M.; Sarson, Mohammad Taufik Zulfikar (CV. ITTC INDONESIA, 2023)
Communities who cannot afford to have the same rights to obtain legal protection as people who are financially able. The purpose of this writing is to find out the Role of Legal Aid Institutions for Poor People in Gorontalo in Civil Case Cases. The research method used in this paper is normative legal research. Legal aid institutions can assist disadvantaged communities in various aspects of civil cases, including providing legal advice, filing lawsuits, providing legal representation in court, and providing legal assistance during the judicial process. Efforts to strengthen legal aid institutions and increase access to justice must continue to be made in order to maintain justice and the sustainability of the legal system.